Revitalizing Sharia Advocates: Reforming the Law on Advocates in Strengthening the Role of Islamic Law in Indonesia - Panjaitan, Budi Sastra; Hasibuan, Putra Halomoan; Kurniawan, Puji; Sirait, Adi Syahputra; Ma'mun, Sukron (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This study aims to evaluate the urgent need to restore the Law of the Republic of Indonesia Number 18 of 2003 concerning Advocates (UUA) to position Sharia advocates as the exclusive legal representatives in religious courts. The research uses a normative juridical method, focusing on the examination of legal norms, rules, and relevant literature. Data were collected through a comprehensive review of legal documents, statutes, and academic sources, and analyzed qualitatively to interpret and critique the legal provisions and their implications. The findings reveal that the current lack of specificity in the advocate profession, particularly in religious courts, has led to the involvement of advocates who may lack the necessary background in Sharia law, potentially harming the legal interests of Muslim clients. The conclusion emphasizes that restoring the Law of the Republic of Indonesia Number 18 of 2003 concerning Advocates to recognize only Sharia advocates in religious courts aligns with the nature of these courts and does not violate human rights. This restoration is vital for protecting the legal interests of Muslims and enhancing the professionalism of Sharia advocates in religious courts, including preparing students of the Faculty of Sharia for specialized legal roles. By promoting legal reforms, the study improves the efficiency of religious courts and ensures better access to justice for Muslim communities.